Traumatic tricuspid regurgitation following equine related blunt chest trauma and review of the literature. Issue 8 (21st August 2021) - Sunthankar, Sudeep; Acheampong, Benjamin; Flack, English
Abstract: Myocardial injury following blunt chest trauma may be difficult to detect. We advocate for cardiac screening in such scenarios. Observation versus intervention should be based on symptoms and the degree of intracardiac disease. Abstract : Myocardial injury following blunt chest trauma may be difficult to detect. We advocate for cardiac screening in such scenarios. Observation versus intervention should be based on symptoms and the degree of intracardiac disease.